Systematic Literature Review: Parenting Stress in Mothers of Children with ADHD, ASD, ID - Esthi Rahayu; DYP Sugiharto; Edy Purwanto; Awalya Awalya (Universitas Negeri Semarang, 2022)
Abstract. Based on the results of previous studies, informing that parents who have children with developmental disorders experience greater parenting stress than parents who care for normal children. Mothers experience more parenting stress than fathers. This study aims to determine the factors that cause the emergence of parenting stress in mothers. To obtain these data, the researchers used a systematic literature review of international journals (data base: Sage, Science Direct, Emerald Insight, Taylor and Francis) in 2011-2021. This method is what distinguishes this research from previous research. Previous research, in looking for factors using interviews. The result of SLR is that there are internal factors (example: understanding of diagnosis, coping strategies) and external factors (example: family resilience, social support of friends) that form parenting stress on mothers. Therefore, the suggestion for future researchers is to provide interventions that are able to suppress the emergence of factors. For example with cognitive behavior therapy intervention.